FEASIBILITY ANALYSIS OF AN AGROINDUSTRY OF STRAWBERRY JELLY IN SÃO JOÃO DA BOA VISTA IN SÃO PAULO - da Silva, Yuri Vascon; Alves, Marcos Rafael; Cavichioli, Fabio Alexandre (Revista Interface Tecnológica, 2023)
The production of jellies is an alternative that allows increasing the shelf life of products, whose base is fruits that are normally perishable and need very specific ways to be transported, which ends up costing their commercialization. As a result, people at national and international level have been incorporating these products into their daily lives and forecasts are that they will increase by up to 12% in the coming years. The objective of the work is to address concepts inherent to strawberry jam, present an investment projection in a strawberry enterprise and present the result of a financial feasibility study for a strawberry jam business. The methodology used was the bibliographic review for content formation and the descriptive research to collect data and process them to generate information. For this project, an investment of R151,482.50 was estimated, with a payback period of 3 years and 7 months, with a net present value of R240,719.37, with an internal rate of return of 36% and an ROI of 77% , taking into account a minimum rate of attractiveness of 10% per year. Being a viable option to carry out an investment over a period of ten years.